Pengembangan Aplikasi Pengelolaan Laboratorium Komputer Dengan Menggunakan Metode Conten Based Filtering Berbasis WEB - Endra Suseno; Erik Kurniadi; Dede Irawan (NUANSA INFORMATIKA, 2024)
The computer laboratory management application plays an important role in managing computer laboratory resources, such as scheduling, equipment maintenance, and usage monitoring. In today's digital era, the development of computer laboratory management applications must take into consideration the need for efficiency and effectiveness in management. Therefore, in this research, a computer laboratory management application will be developed using the web based Content Based Filtering method. The Content Based Filtering method will assist in managing the computer laboratory usage schedule by considering the preferences and needs of each user. This application is developed using the PHP programming language and the CodeIgniter framework. The results of this research are expected to help computer laboratory managers improving the efficiency and effectiveness of computer laboratory management.